PELAKSANAAN HAK-HAK KESEHATAN FUNGSI REPRODUKSI DITINJAU DARI ASPEK HUKUM KETENAGAKERJAAN ( STUDI KASUS PADA PEKERJA WANITA DI SEMARANG ) (Fokus Ekonomi, 2008)
In Indonesia attempts to make the best use of women in terms of employment opportunity and at the same time to give them their basic rights as women have been ruled out in the law of employment with respect to their   reproduction system. For example, they may get days off on the first and second day of their circular period, maternity and legal abortion leaves. Breastfeeding on job is also allowed. No working hours between 23.00 p.m to 07.00 a.m. However, violation of such rules still occurs on the part of the company, such as done with respect to the right of leaves during monthly period. This has been caused by the imbalance of the number of supervisors as compared to the number of companies and rules-violators. Besides, no rules violators have been put to court for justice ith respect to failing to comply with the rules to give women’s right of reproduction system. Key words: Rights, Reproduction Fuction,. Violation, Supervision  and  Sanction.